Gerhardtia tomentosa and Ossicaulis borealis (Agaricales, Lyophyllaceae)—Two new species from northeast China - Qi, Yue; Xu, Fei; Yang, Zhao-Qian; Hou, Jian-Xuan; Xu, Ai-Guo; Guo, Hong-Bo; Yu, Xiao-Dan; Yang, Rui-Heng (Frontiers in Microbiology, 2023)
Gerhardtia tomentosa and Ossicaulis borealis, within the family Lyophyllaceae, are described from northeastern China. Gerhardtia tomentosa is characterized by its tricholomatoid basidiocarps with cream to yellowish gray pileus with minute, white tomentose surface, cream lamellae, whitish to light brown stipe with basal tomentum, smooth or minutely verrucose and slightly undulate basidiospores measuring (5.0–) 5.5–6.5 (–7.2) × (1.8–) 2.0–3.0 (–3.2) μm and absence of cystidia. Ossicaulis borealis is featured by its medium to large basidiomata, white to grayish orange to brownish orange pileus, white to grayish orange lamellae, central to eccentric stipe, irregularly reticulate basidiospores measuring (2.8–) 3.0–4.0 × (–1.8) 2.0–2.4 (–2.8) μm and absence of cystidia. Phylogenetic placement of the two species was determined by the combined datasets containing ITS and nrLSU regions, and the results showed that collections of the two species formed two independent lineages in each genus. A morphological comparison was also performed between the two species and all other taxa of the two genera. A theoretical basis is provided for the two lyophylloid genera that show an apparently poor species diversity worldwide.